A rare case of infectious mononucleosis complicated by Guillain-Barre syndrome - Margaret Kennedy; Mariya Apostolova (MDPI AG, 2013)
Infectious mononucleosis is a clinical syndrome characterized by fever, lymphadenopathy and pharyngitis. Neurologic complications of infectious mononucleosis, such as the development of Guillain-Barre syndrome, have been rarely reported and usually present late in the course of the disease. We describe a case of a 29 year old male with no significant past medical history who was diagnosed with Guillain-Barre syndrome following an infection with Epstein-Barr virus associated infectious mononucleosis. Supportive treatment resulted in full recovery.